Fiqih Siyasah Prinsip-Prinsip Fiqih Siyasah dalam Konstitusi Republik Indonesia - Shofiyah, Roidatus; Samuji; Yulianis, M. Sifa Fauzi; Murniati, Dewi; Abdul Majid, Amir Bandar (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2024)
This article discusses the implementation of the principles of siyasah fiqh in the Constitution of the Republic of Indonesia. These principles refer to the use of Islamic law in regulating political and governmental issues. This article explores how these principles are reflected in the Indonesian legal system which covers various aspects such as social justice, public morality and governance. This research uses a documentary analysis and literature study approach. The main data collected is the text of the constitution of the Republic of Indonesia, especially focusing on articles relating to the principles of siyasah fiqh. By analyzing the text of the constitution and the views of experts, this article shows the relevance and application of the principles of siyasah fiqh in the current context of Indonesian positive law.